Interbody Fusion in Low Grade Lumbar Spondylolsithesis: Clinical Outcome Do Not Correalte with Slip Reduction and Neural Foraminal Dimension. Issue 1 (April 2016) - Debnath, Ujjwal K.; McConnell, Jeffrey R.; Goel, Vivek
Introduction: There is no consensus in literature whether a beneficial effect of reduction on outcome can be expected following reduction and surgical fusion for low grade lumbar spondylolisthesis. This prospective study was designed to find a possible correlation between the clinical outcome and extent of lumbar spondylolisthesis reduction. Material and Methods: 52 patients (age 17–48 years) with isthmic spondylolisthesis underwent interbody fusion with cages with posterior instrumentation (TLIF or PLIF). Clinical outcome was measured using Visual Analogue Scores (VAS) and Oswestry Disability Index (ODI). Foraminal dimensions and disc heights were measured in standard digital radiographs. These were analyzed at baseline and at 1 year after surgery and changes were compared. Radiographic fusion judged with CT scans at 1 year. Results: 90 percent of the patients in the study had good or very good clinical results with fusion and instrumentation. The baseline and at one year postoperative, the mean VAS scores were 6.39 (range 5–8) and 0.81 (range 0–3) respectively ( p  = 0.004). The baseline and at one year postoperative, the mean ODI scores were 48 (range 34–58) and 9.8 (range 4–22) respectively ( p  < 0.001). A mean spondylolisthesis slip of 33.2% was reduced to 6.7% at 1 year. Average anterior disc height, posterior disc height, C distance, F diameter improved from 9.4mm to 11.7mm ( p  = 0.005), from 4.3mm to 5.8mm( p  = 0.004), from11.2mm to 12.0mm( p  = 0.002), from 18.5mm to 19.4mm respectively( p  < 0.001). The fusion rate was 66% with PLIF and 75% with TLIF. There is no significant correlation between the improvements of ODI scores and the extent of slip reduction. Conclusion: Neural decompression and interbody fusion significantly improved pain and disability but the clinical outcome does not correlate with radiological improvement in neural foraminal dimension.